Challenging depressive beliefs: Habitual and recollective components of stability or change. (September 2022) - Hertel, Paula; Acuff, M. Chase; Hernandez, Jessica; Poppe, Elizabeth
Abstract: Background and objectives: Depressed people tend to hold stable negative beliefs that resist challenges. Two experiments investigated the cognitive bases of belief change or resistance to change following the provision of supportive or challenging pseudo-evidence. Method: Students scoring high and low on a measure of depressed state read belief statements, each followed by invented experimental evidence to either verify or discount them. Two days later, they read all the belief statements again, together with new statements, this time rating belief. Results: The students agreed that the statements described common beliefs and that the evidence was plausible. Discounted statements were believed less than new statements on the test. Also, dysphoric students believed discounted and new statements less than verified statements, but that difference was larger for the nondysphoric students. Parameter estimates of the habitual basis for belief ratings, obtained with process-dissociation procedures, were higher in the dysphoric group, and estimates of evidence recollection were lower. The latter finding was conceptually supported by deficient recognition of the gist of the discounting evidence in the dysphoric group (Experiment 2). Limitations: Experiment 2 results replicated the rating effects in Experiment 1, but not the parameter differences, due to low power as a consequence of the university response to the pandemic. Conclusions: We interpret these results in the context of other evidence regarding belief change and depressive cognition, such as habitual rumination and deficient cognitive control. Highlights: "Invented" research evidence verified or discounted common negative beliefs. The habit component of belief change was larger in the dysphoric group. The component termed evidence recollection was smaller in the dysphoric group. In Experiment 2, dysphoric students recognized the gist of the evidence less well.